STUDI PERBANDINGAN PENGGUNAAN MEDIA SOSIAL DAN FORUM DISKUSI DARING DALAM MENINGKATKAN INTERAKSI DAN KOLABORASI ANTAR MAHASISWA DI PERGURUAN TINGGI - Damayanti, Desy; Nuzuli, Ahmad Khairul (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This study aims to compare the use of social media and online discussion forums as tools to enhance interaction and collaboration among students in higher education institutions. The research method employed is a quantitative approach with an experimental research design. The research sample consists of two groups of students, one group using social media as a means of interaction and collaboration, and the other group using online discussion forums. Data were collected through questionnaires measuring the level of interaction and collaboration among students in each group. Additionally, data were gathered through participatory observation to directly observe interactions. Data analysis was conducted using appropriate statistical techniques to compare the differences between the two groups. The results indicate that both groups of students experienced increased interaction and collaboration after using social media and online discussion forums. However, there was no significant difference in the increase of interaction between the two groups. Nevertheless, a significant difference was found in the level of collaboration, with the group using online discussion forums showing a more significant increase in collaboration compared to the social media group. These findings suggest that both social media and online discussion forums are effective in enhancing interaction among students in higher education institutions, but online discussion forums are more effective in fostering better collaboration among them. This study provides important insights for educational institutions in choosing and optimizing the use of communication platforms to enhance student interaction and collaboration. It also highlights the potential of online discussion forums as an effective tool in creating a more collaborative learning environment in higher education. Keywords : Social Media, Online Discussion Forums, Student Interaction